Improving intercultural communication skills: A challenge facing institutions of higher education in the 21st century - Chai K. Kim (Technische Universität Braunschweig, Institut für Marketing, 1999)
Following discussion of the rationales for improving students' intercultural communication skills, this article described how the professors at the University of Rhode Island and their counterparts around the world use the Internet as a mechanism for improving a student's intercultural awareness and sensitivity. Using the Internet, students here and abroad debate on timely, relevant topics to become aware of how people of different cultures see things differently. In addition, they write and exchange cross-cultural dialogues and explanatory notes to become interculturally sensitive. In this way, the students meet with their future partners of the global workplace, while honing their computer skills, writing skills, and enhancing their intercultural awareness and sensitivity. However, those in higher education who want to implement this kind of Internet-based teaching technique on a permanent basis must first address several difficult issues, including how to find like-minded professors here and abroad who are willing to participate. If correctly used over time, these techniques (international e-mail debate and cross-cultural dialogues) can improve students' intercultural awareness and sensitivity. Assessment of whether or not this improvement lasts over a period of time presents a quantitative problem. Defining intercultural sensitivity practically and satisfactorily is the first task facing educators interested in following this path toward improved communication. One of the greatest challenges facing the institutions of higher education of the 21st Century is how to improve intercultural communication skills of their students. Accompanied by a yet-to-be-developed instrument for quantitative measurement of long-term outcomes, projects like the international e-mail debate and cross-cultural dialogue may well become the tools for understanding and negotiation in the new global environment.
Keywords: 650